Performance of 18F-FET versus 18F-FDG-PET for the diagnosis and grading of brain tumors: systematic review and meta-analysis. Issue 3 (4th August 2015) - Dunet, Vincent; Pomoni, Anastasia; Hottinger, Andreas; Nicod-Lalonde, Marie; Prior, John O.
Abstract: Background: For the past decade 18 F-fluoro-ethyl-l -tyrosine (FET) and 18 F-fluoro-deoxy-glucose (FDG) positron emission tomography (PET) have been used for the assessment of patients with brain tumor. However, direct comparison studies reported only limited numbers of patients. Our purpose was to compare the diagnostic performance of FET and FDG-PET. Methods: We examined studies published between January 1995 and January 2015 in the PubMed database. To be included the study should: (i) use FET and FDG-PET for the assessment of patients with isolated brain lesion and (ii) use histology as the gold standard. Analysis was performed on a per patient basis. Study quality was assessed with STARD and QUADAS criteria. Results: Five studies (119 patients) were included. For the diagnosis of brain tumor, FET-PET demonstrated a pooled sensitivity of 0.94 (95% CI: 0.79–0.98) and pooled specificity of 0.88 (95% CI: 0.37–0.99), with an area under the curve of 0.96 (95% CI: 0.94–0.97), a positive likelihood ratio (LR+) of 8.1 (95% CI: 0.8–80.6), and a negative likelihood ratio (LR−) of 0.07 (95% CI: 0.02–0.30), while FDG-PET demonstrated a sensitivity of 0.38 (95% CI: 0.27–0.50) and specificity of 0.86 (95% CI: 0.31–0.99), with an area under the curve of 0.40 (95% CI: 0.36–0.44), an LR+ of 2.7 (95% CI: 0.3–27.8), and an LR– of 0.72 (95% CI: 0.47–1.11). Target-to-background ratios of either FDG or FET, however, allow distinction between low- and high-grade gliomas ( P > .11). Conclusions: For brain tumor diagnosis, FET-PET performed much better than FDG and should be preferred when assessing a new isolated brain tumor. For glioma grading, however, both tracers showed similar performances.